2016
DOI: 10.1259/dmfr.20160136
|View full text |Cite
|
Sign up to set email alerts
|

The use of magnetic resonance imaging in the evaluation of upper airway structures in paediatric obstructive sleep apnoea syndrome: a systematic review and meta-analysis

Abstract: English assessing the use of MRI integrated with traditional polysomnography (PSG) among children up to 15 years of age affected by OSAS. The primary outcome to be evaluated was the efficacy of MRI in analyzing the upper airway total volume among healthy children compared with children affected by OSAS. Secondary outcomes were to compare the efficacy of MRI in analyzing the upper airway cross-sectional area in the areas adjacent to the adenoids and tonsils, adenoid and tonsil volume, and soft-tissue and maxill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…Reduction in airway volume is a risk factor for obstructive sleep apnea (OSA). Patini, R. et al, confirmed that children with OSA could undergo MRI assessment to effectively analyze the tonsil and airway patterns [20]. This is supported by the finding that airway stenosis is observed at the level of the velopharynx and oropharynx in many patients with OSA [21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 86%
“…Reduction in airway volume is a risk factor for obstructive sleep apnea (OSA). Patini, R. et al, confirmed that children with OSA could undergo MRI assessment to effectively analyze the tonsil and airway patterns [20]. This is supported by the finding that airway stenosis is observed at the level of the velopharynx and oropharynx in many patients with OSA [21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 86%
“…Lee et al [21] investigated the use of CT for evaluating masseter muscle changes following orthognathic surgery; even though this method can be considered as the one giving the most well-defined images of muscular structures it should be avoided in a population of growing subjects for ethical reasons. In fact, as demonstrated by some authors [37] MRI is effective in showing soft components of head and neck region, but its application is currently limited to the study of masticatory activity and there is no evidence of its use during orthodontic treatment [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Constantly wearing the aligners, a slight modification of the vertical dimension could have beneficial effect also in the intra-articular compression, even with a repositioning of the joint ( 8 ). Positive effects are also reported in patients affected by obstructive sleep apnoea syndrome whose diagnosis is even more complex in the event of a decrease of the vertical dimension ( 9 ).…”
Section: Discussionmentioning
confidence: 99%